Judgment Day: The Workers’ Stage and the Popular Front in 1930s Finland - Seppälä, Mikko-Olavi (Nordic Theatre Studies, 2018)
The Workers’ Stage (in Finnish ‘Työväen Näyttämö’) was an amateur workers’ theatre based in Helsinki. The theatre experienced its height of success when it co-operated with left-wing intellectuals between 1934 and 1939. As an organic part of the Popular Front movement, the theatre brought an international anti-fascist repertoire to Finland. In the performance of Elmer Rice’s Judgment Day (1935) the struggle for civil rights in Finland was put in the larger frame of the international struggle against Fascism. Uniting intellectuals and workers, the theatre and its activist personnel also functioned as a platform for the practical organising of counter-hegemonic intervention and underground activism. For the activist left-wing opposition, theatre functioned as an extension of their political journals, as a (counter-)public sphere and a vehicle for highlighting contemporary political problems, accelerating public discussion and engaging more people – workers and intellectuals alike – in fruitful interaction. The activism had clear political results in the 1936 elections, although the personal outcome for the activist artists and communists turned out to be controversial, as they remained rejected from the new hegemony.